Barriers to quality patient care in rural district hospitals - Johanna E. Eygelaar; Ethelwynn L. Stellenberg (AOSIS, 2012)
Currently barriers exist in delivering quality health care. This study aimed to investigate such barriers in the eight rural district hospitals of the West Coast Winelands Region, three type A and five type B hospitals. A quantitative descriptive design was applied which included the total population of nursing staff (n = 340) working at the time of data collection. A self-administered questionnaire was distributed with a response rate of 82%. Reliability of the instrument was verified using the Cronbach alpha coefficient and a pilot study. The validity, specifically construct and content validity, were assured by means of an extensive literature review, pilot study and use of experts. Ethics approval was obtained from the relevant stakeholders. Results showed that 272 participants (97%) disagreed that provision of staff was adequate, with staff above 40 years of age more likely to disagree (p = <0.01). A statistically significant association was shown between availability of doctors and staff not being able to cope with emergencies (p = <0.01). Most participants (n =212; 76%) indicated that they were not receiving continuing education, with the registered nurses more likely to disagree (χ² test, p = 0.02). Participants in both hospital types A (n = 131; 82%) and B (n = 108; 91%) also disagreed that provision of equipment and consumables was adequate. The research showed that inadequacies relating to human resources, professional development, consumables and equipment influenced the quality of patient care. Urgent attention should be given to the problems identified to ensure quality of patient care in rural hospitals.